Policies for Poverty Reduction, Sustainable Land Management, and Food Security: A Bioeconomic Model with Market Imperfections - Holden, Stein; Shiferaw, Bekele A.; Pender, John L. (International Food Policy Research Institute, 2006)
Ethiopia is one of the poorest countries in the world, and its population of more than 70 million people lives mostly in the highlands. The food security of these people is threatened by land degradation and droughts that cause declining and highly variable land productivity. Changes in the global climate may also have caused an increase in the incidence of drought that has occurred recently in areas that were not affected by the earlier droughts. Along with a history of social conflict and unrest in the country, poor governance and misplaced government policies have contributed to the vicious spiral of poverty, land degradation, and food insecurity. There is a strong need for peace, better governance, and improved policies that can help break the Malthusian development path and put communities onto more sustainable development pathways where poverty is reduced and food security is improved. Especially, there is an urgent need for pro-poor alternative development strategies that address land degradation and food insecurity in less-favored areas where drought risk is higher and/or market access is poorer.